2018
DOI: 10.1155/2018/9365174
|View full text |Cite|
|
Sign up to set email alerts
|

[18F]ML-10 Imaging for Assessment of Apoptosis Response of Intracranial Tumor Early after Radiosurgery by PET/CT

Abstract: [18F]ML-10 is a novel apoptosis radiotracer for positron emission tomography (PET). We assess the apoptosis response of intracranial tumor early after CyberKnife (CK) treatment by [18F]ML-10 PET imaging. 29 human subjects (30 lesions), diagnosed with intracranial tumors, underwent CK treatment at 14–24 Gy in 1–3 fractions, had [18F]ML-10 positron emission tomography/computed tomography (PET/CT) before (pre-CK) and 48 hours after (post-CK) CK treatment. Magnetic resonance imaging (MRI) scans were taken before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…All lesions studied were detected by 18 F-ML-10 PET and a highly significant correlation was found between early changes on the 18 F-ML-10 scans and later changes in tumour anatomical dimensions assessed using sequential MRI-imaging. Similar results were obtained by Sun et al in a study of 29 patients, diagnosed with intracranial tumours that underwent a cyberknife treatment at 14-24 Gy in 1-3 fractions, as well as a baseline and 48 h post-treatment 18 F-ML-10 PET scan [48]. It was found that malignant tumours tended to be more sensitive to the CK treatment but that the treatment outcome was not affected by the pre-CK apoptotic status of tumour cells, as assessed using 18 F-ML-1P PET.…”
Section: Cell Membrane Acidification Targeting Radioligandssupporting
confidence: 88%
“…All lesions studied were detected by 18 F-ML-10 PET and a highly significant correlation was found between early changes on the 18 F-ML-10 scans and later changes in tumour anatomical dimensions assessed using sequential MRI-imaging. Similar results were obtained by Sun et al in a study of 29 patients, diagnosed with intracranial tumours that underwent a cyberknife treatment at 14-24 Gy in 1-3 fractions, as well as a baseline and 48 h post-treatment 18 F-ML-10 PET scan [48]. It was found that malignant tumours tended to be more sensitive to the CK treatment but that the treatment outcome was not affected by the pre-CK apoptotic status of tumour cells, as assessed using 18 F-ML-1P PET.…”
Section: Cell Membrane Acidification Targeting Radioligandssupporting
confidence: 88%
“…Several small-molecule imaging probes that detect cell or mitochondrial membrane depolarisation and/or acidification of apoptotic cells have also been developed. In patients with intracranial tumours, the change in 18 F-ML-10 uptake from before to 48 h after CyberKnife stereotactic radiotherapy correlated with the decrease in tumour volume measured at 2–4 months after treatment [25]. Similar correlations have been made in patients with brain metastases imaged before and nine days after whole-brain radiotherapy [26].…”
Section: Imaging Apoptosis and Necrosismentioning
confidence: 73%
“…Indeed, this inflammation leads to two phenomena: an activation of the immune system which will induce an increase in blood flow and an acidification of the microenvironment due to the release of immune cells and cytokines [34]. As a consequence, precedent clinical trials used [ 18 F]ML-10 for PET imaging of apoptosis following radiotherapy treatments [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…The [ 18 F]ML-10 radiotracer is highly stable in vivo and presents a rapid clearance from non-targeted organs and a favorable dosimetry profile [19]. Several clinical trials have recently evaluated [ 18 F]ML-10 for early detection of response to radiation therapy in patients with brain metastases [20,21]. In those studies, early treatmentinduced changes in the [ 18 F]ML-10 tumor accumulation were measured by voxel-based analysis and correlated with changes in anatomical dimensions, as visualized with magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%